2010
DOI: 10.1111/j.1600-6143.2010.03265.x
|View full text |Cite
|
Sign up to set email alerts
|

Renal Failure Five Years After Lung Transplantation Due to Polyomavirus BK‐Associated Nephropathy

Abstract: Polyomavirus-associated nephropathy (PyVAN) is rare in nonrenal solid organ transplantation and only limited information is available from single cases. We describe a 67-year-old female presenting with hypertension and progressive kidney failure due to Py-VAN 60 months after lung transplantation. Plasma BK virus (BKV) loads were 4.85 log 10 copies/mL at diagnosis and cleared slowly over 14 months after switching from tacrolimus, mycophenolate and prednisone to low-dose tacrolimus, sirolimus and leflunomide, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 39 publications
(18 reference statements)
0
32
0
1
Order By: Relevance
“…Clinical impact is relevant, as loss of the renal graft ranges from 30% up to > 80% of cases [12][13][14] ; in transplant centres where screening for polyomavirus replication in the urine and plasma is performed, the rate of graft loss is lower [15] . Several studies evidenced that BK viremia is only rarely observed in non-kidney solid organ transplant recipients and biopsy-confirmed cases of nephropathy have been described in few case reports [16][17][18][19][20][21][22] , despite the similar or even higher level of immunosuppression, thus supporting the role of organ determinants in the pathogenesis of PVAN.…”
Section: Human Polyomaviruses and Nephropahtymentioning
confidence: 99%
“…Clinical impact is relevant, as loss of the renal graft ranges from 30% up to > 80% of cases [12][13][14] ; in transplant centres where screening for polyomavirus replication in the urine and plasma is performed, the rate of graft loss is lower [15] . Several studies evidenced that BK viremia is only rarely observed in non-kidney solid organ transplant recipients and biopsy-confirmed cases of nephropathy have been described in few case reports [16][17][18][19][20][21][22] , despite the similar or even higher level of immunosuppression, thus supporting the role of organ determinants in the pathogenesis of PVAN.…”
Section: Human Polyomaviruses and Nephropahtymentioning
confidence: 99%
“…For example, in lung-transplant recipients, it is reported that 9% will have ESRF and 53% double their serum creatinine by 5 years posttransplant (130,184). Although this is most commonly an effect of calcineurin antagonist, other transplant-specific factor such as infection with polyomavirus BK may be important (73).…”
Section: Other Factorsmentioning
confidence: 98%
“…The impact of BKV on kidney function and long-term outcomes in nonrenal SOT recipients is not well established (113,114). Although case reports of potential BKV-associated nephropathy in native kidneys, mainly of heart and lung transplant recipients, have been published (115)(116)(117), the majority of studies prospectively assessing the role of BKV in nonrenal SOT recipients have found low rates of BKV viremia and no association between BK viruria and renal dysfunction (113,114,(118)(119)(120)(121).…”
Section: Type Of Organ Transplantmentioning
confidence: 99%